THE ROLE OF COST OF CAPITAL IN THE LINK BETWEEN ESG REPORTING AND FIRM PERFORMANCE - Dwomor, Emmanuel; Mensah, Emmanuel (Jurnal Akuntansi dan Keuangan Indonesia, 2024)
The attention surrounding Environmental, Social, and Governance (ESG) factors within the corporate realm has grown significantly, as evidence mounts regarding their influence on firm performance. This research explores the connection between ESG reporting and firm performance from emerging economies’ perspective, with the cost of capital acting as a mediator to enhance our understanding of how capital providers perceive the risk profile of ESG-compliant firms and thereby reward them through a reduction in the costs they demand on their invested capital. The study sourced annual reports data on a sample of 146 emerging market firms across 59 industries spanning 2019 to 2022 from 18 emerging economies. ESG data was sourced from Sustainalytics database. Panel data models were used in the analysis. The study discovers a positive link between ESG reporting and firm performance, indicating that companies with robust ESG reporting tend to fare better financially. Moreover, it identifies a negative relationship between ESG reporting and the cost of capital, implying that stronger ESG reporting practices lower a firm’s cost of capital. Additionally, the study ascertains the mediating role of the cost of capital in the relationship between ESG reporting and firm performance, emphasising its significance in shaping the financial outcomes of firms in emerging economies. The study extends stakeholder and legitimacy theories to emerging economies, emphasizing their adaptability. It highlights the mediating role of the cost of capital in the ESG-performance relationship, contributing to the literature. Practically, it shows ESG-compliant firms as lower-risk investments, offering guidance to investors and informing policymakers to foster ESG adoption and sustainability through regulations.